Economic Study Of Tuna Loin Industry Development In Kaur Regency, Bengkulu Province - Zamdial Zamdial; Dede Hartono; Tri Anugrah Yudesta (Journal of Aquaculture Science, 2021)
Tuna fishery production in Bengkulu Province is mainly produced by fishermen in Kaur Regency. The tuna fishery business in Kaur Regency is still small scale and traditional. The potential of tuna fish resources that quite large in the Kaur Regency waters, which provides a large enough opportunity for the development of tuna fisheries to a larger scale, including the tuna processing industry. The research objective was to analyze the feasibility of developing the tuna loin industry in Kaur Regency, Bengkulu Province. The research was conducted in July-August 2018, using a survey method. Data collection was carried out by observation and interview methods. Data analysis was carried out by descriptive method. The feasibility assessment of developing a tuna loin industry using 4 investment criteria, namely B/C Ratio, NPV (Net Present Value), Internal Rate of Return (IRR), and Payback Period (PP). The calculation result of the 4 investment criteria for development of tuna loin fishery industry in Pasar Lama Village, Kaur Regency, Bengkulu Province, namely Net B/C ratio = 1.13, NPV = 594,414,281, IRR = 16.20 and PP = 2.9. Based on the value of 4 investment criteria, with the support of raw material availability and marketing aspects, the development of the tuna loin industry in Pasar Lama Village, Kaur Regency, Bengkulu Province is feasible to be developed.Keywords: tuna, loin, industry, investment, Kaur, Bengkulu